The value of forest fragments within or surrounding oil palm plantations and disturbed landscapes for terrestrial mammal conservation in Sabah, Malaysia - Tung, Siaw Ean (2020)
Logging and forest conversion to oil palm plantations in Southeast Asia have resulted in the formations of numerous small isolated forest fragments scattered within or surrounding converted habitat landscapes. Although large areas have been affected, little is known about their impacts on the native small mammal fauna. By using standardised grid trapping techniques and Generalised Linear Mixed-Effects modelling (GLMM), the species richness, abundance and diversity of the small mammals at ten forest fragment sites i.e. five in selectively logged forest fragments (12-88 ha) and five in unlogged forest fragments (45-3529 ha), were compared with four continuous forest sites i.e. two in continuous selectively logged forest and two in continuous unlogged primary forest (>800000 ha) in the lowland areas in eastern Sabah, Malaysian Borneo. The objectives were to assess the effects of logging and forest fragmentation on aspects of community structure of the small mammals. Additionally, the effects of fragment size, degree of isolation as well as aspects of forest quality were also investigated. Non-matrix Multidimensional Scaling (NMDS) plot was used to discern the small mammal assemblage composition by forest type treatments. In general, unlogged forests had significantly higher small mammal species richness and diversity compared to that of logged forests. Irrespective of the forest conditions, significantly fewer species but higher abundance of small mammals were recorded in forest fragments compared to continuous forests. In terms of species composition, forest fragments (both logged and unlogged) were dominated by common and widespread species, whereas rare species were more represented in the continuous forest sites. The effects of forest isolation and forest quality on the small mammals’ community were not significant. Overall, the present study revealed the negative effects of logging and forest fragmentation on the small mammal community. However, forest fragments are still valuable for conserving many common native species of small mammals that are adapted to living in disturbed forest. Given that converted habitats, such as oil palm plantations, and other disturbed landscapes are generally species poor in terms of the native small mammal fauna, retaining forest fragments within or surrounding converted habitat landscapes may mitigate the loss of local biodiversity resources to some extent.